The importance of the concept of permission in the normative systems and the framework of constitutional states - Ku Yanasupo, Lily (2020)
This research analyzes the importance of the concept of permission in normative systems based on the idea that it does not only mean absence of prohibition, and that the notions of prohibition / obligation are not enough to explain these systems. In this sense, taking as main referent the classical theory of Carlos E. Alchourron and Eugenio Bulygin on the meanings of the deontic term “permitted” according to its prescriptive and descriptive use, as well as the distinction between the field of the normative systems and the field of legal reasoning, the author suggests that although a “non-prohibited conduct” can be interpreted as an “permitted conduct”, this interpretation is not sufficient to consider that such conduct is regulated and available to the subject. Regarding the practical analysis of permissive rules, mainly in the framework of constitutional states, the author explains the utility of these to close the legal systems, generate the obligation to facilitate or the prohibition of not interfering in the action referred in the permit, and delimit the normative powers when there are hierarchically ordered authorities.